A survey of subcutaneous blood flow in patients with SMID and subcutaneous ceftazidime administration using mentholated warm compresses in healthy subjects. (April 2016) - Ebihara, Tsuyoshi; Oshima, Shinji; Yasuda, Yuko; Okita, Mitsuyoshi; Ohara, Kousuke; Negishi, Akio; Ohshima, Shigeru; Iwasaki, Hiroyuki; Yoneyama, Akira; Kitazumi, Eiji; Kobayashi, Daisuke
Objectives: To investigate subcutaneous blood flow rate (SBFR) in healthy volunteers and patients with severe motor and intellectual disabilities (SMID), and evaluate the effect of mentholated warm compresses (MWCs) on SBFR and subcutaneous ceftazidime absorption in healthy volunteers. Methods: SBFR at the forearm, chest and abdomen were evaluated in Japanese healthy volunteers and in adults with SMID. The effects of MWCs on blood flow rate and ceftazidime pharmacokinetics were evaluated in healthy volunteers. Results: SBFR was significantly lower in the forearms of female patients with SMID ( n = 11) than in the forearms of healthy females ( n = 6); it was not significantly lower in the abdomen or chest. There were no significant differences between male patients ( n = 18) or controls ( n = 12) in SBFR at any site. MWC application increased SBFR 1.3- to 2.0-fold compared with baseline in healthy controls ( n = 6). MWC application increased ceftazidime maximum blood concentration, SBFR and time above mutant prevention concentration in a single healthy subject. Conclusions: Abdominal SBFR in patients with SMID did not differ from that of healthy subjects. MWC application increases SBFR and subcutaneous drug absorption rate in healthy humans.